Brain specific Lamellipodin knockout results in hyperactivity and increased anxiety of mice - Bodo, Cristian (Sci Rep, 2017)
Lamellipodin (Lpd) functions as an important signalling integrator downstream of growth factor and axon guidance receptors. Mechanistically, Lpd promotes actin polymerization by interacting with F-actin and the actin effectors Ena/VASP proteins and the SCAR/WAVE complex. Thereby, Lpd supports lamellipodia protrusion, cell migration and endocytosis. In the mammalian central nervous system, Lpd contributes to neuronal morphogenesis, neuronal migration during development and its C. elegans orthologue MIG-10 also supports synaptogenesis. However, the consequences of loss of Lpd in the CNS on behaviour are unknown. In our current study, we crossed our Lpd conditional knockout mice with a mouse line expressing Cre under the CNS specific Nestin promoter to restrict the genetic ablation of Lpd to the central nervous system. Detailed behavioural analysis of the resulting Nestin-Cre-Lpd knockout mouse line revealed a specific behavioural phenotype characterised by hyperactivity and increased anxiety.